SPECIAL ASPECTS OF PERSONAL REHABILITATIVE RESOURCES OF ACTUAL AND DEMOBILIZED MILITARY SERVICE MEMBERS - Prokofieva, Olesia; Koshova, Inna; Prokofieva, Olga (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the results of the empirical study on personal rehabilitative resources of actual and demobilized military service members (coping strategies, strategies of resistance, psychological hardiness). The combat experience of actual and demobilized military service members leads to severe personality traumas, appeared symptoms of post-traumatic stress disorders, severe tension of their adaptive potential. The situation can be controlled with active problem- and emotionally-focused coping strategies in order to transform the situation, rather than to escape it. In particular, these are the strategies involving positive re-appraisal, plannful problem solving, and increased self-control. Several gender differences in the use of copings were identified. The study shows that the position focused on effective self-development in the most sustainable. Along with the severe symptoms of maladaptation, the combatants consider also their experience as one that shows the value of life and self-enrichment.